HIV-1 and GBV-C co-infection in Venezuela - Anny Karely Rodriguez; Domingo José Garzaro; Carmen Luisa Loureiro; Cristina R Gutierrez; Gladys Ameli; Rossana Celeste Jaspe; Leticia Porto; Francisca Monsalve; Angela Pozada; Luzmary Vázquez; Miguel E Quinones-Mateu; Flor Helene Pujol; et al. (Journal of Infection in Developing Countries)
Introduction: Co-infection with GB virus C (GBV-C) in patients infected with human immunodeficiency virus 1 (HIV-1) has been associated with prolonged survival. The aim of this study was to evaluate the prevalence of GBV-C infection among HIV-1-infected patients in Venezuela, and to determine the effects of the co-infection on the levels of relevant cytokines. Methodology: Plasma samples were collected from 270 HIV-1-seronegative and 255 HIV-1-seropositive individuals. GBV-C infection was determined by RT-PCR of the NS5 region and genotyped by sequence analysis of the 5´UTR region. HIV-1 strains were characterized by sequence analysis of pol, vif, env, and nef genes. Selected cytokines were evaluated by ELISA. Results: Ninety-seven of 525 (18.5%) plasma samples tested positive for GBV-C RNA. A significantly higher prevalence of GBV-C was found among HIV-1 patients compared to HIV-1-seronegative individuals (67/255, 26% versus 30/270, 11%; p < 0.001). Statistical difference was observed in the viral load between HIV-1+GBV-C+ and HIV-1+GBV-C- (p = 0.014), although no differences in CD4+ cell counts were found between both groups. TNFα concentration was higher in HIV-1+GBV-C- than in HIV-1+GBV-C+ patients (25.9 pg/mL versus 17.3 pg/mL; p = 0.02); RANTES expression levels were more variable in GBV-C co-infected patients and more frequently elevated in HIV-1 mono-infected patients compared to patients co-infected with GBV-C. Conclusions: The previously observed beneficial effect of co-infection with HIV-1 and GBV-C on disease progression is complex and might be due in part to a change in the cytokine environment. More studies are required to understand the interaction between both viruses.